TINDAK TUTUR EKSPRESIF DALAM FILM JELITA SEJUBA: MENCINTAI KESATRIA NEGARA - Sri Dwi Yulianti; Muhammad Saleh (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Expressive speech acts in the film Jelita Sejuba: Loving the Knights of the Country. This study aims to: (1) describe the form of expressive speech acts in the film Jelita Sejuba: Loving the Kesatria Negara, (2) describe the expressive speech acts in the film "Jelita Sejuba: Loving the Knights of the Country". This type of research is a descriptive qualitative research. The data collection technique was carried out using the listening method and note-taking technique. The results of the research on expressive speech acts in the film Jelita Sejuba revealed that there were 19 forms of expressive speech acts, namely thanking, praising, blaming, suspecting, accusing, insinuating, criticizing, apologizing, speech acts expressing surprise, expressing feelings or surprised, expressing annoyance or irritation, expressing anger, expressing pride, expressing shame, expressing fear, expressing sympathy, and expressing disappointment. Meanwhile, the functions of expressive speech acts are derived from the language functions found in the speech in the film Jelita Sejuba, namely referential functions, emotive functions, and conative functions.